Pengaruh Dukungan Sosial Teman Sebaya terhadap Regulasi Emosi pada Mahasiswa Baru - Rahmatul Ulfa; Rodatul Jannah; Jeni Fadhila; Muzhdhalifatul Azizah; Gita Syawla Indah Fitri; Gustina Rahmawati; Adifa Khoiron (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Emotional regulation is an individual's ability to regulate their emotions and be able to express the emotions they experience. One factor that can influence emotion regulation is peer support. The aim of this research is to examine the influence of peer social support on emotion regulation in new students. The method used in this research is quantitative with simple linear regression data analysis. The sample used in this research was 143 new students majoring in psychology using random sampling technique. The results obtained from this research are that there is an influence of peer social support on emotional regulation in new students of 19.9%.